Analisis Keanekaragaman Fitoplankton dan Zooplankton sebagai Indikator Kualitas Perairan pada Aliran Sungai Semangir Jember - Mira Fujika Hayati; Putri Wulandari; Imaniah Bazlina Wardani (Lembaga Yasin AlSys, 2026)
Rivers, as lotic aquatic ecosystems, are susceptible to changes in environmental quality that can affect plankton community structure. This study aimed to analyze phytoplankton and zooplankton diversity as indicators of water quality in the Semangir River, Jember, and to examine their relationships with the physicochemical parameters of the water. The study employed a descriptive quantitative approach with purposive sampling at three stations representing the upstream, middle, and downstream sections. Samples were collected in the morning, at midday, and in the afternoon on November 14, 2025. Analyses involved plankton identification, individual counts, the Shannon–Wiener diversity index (H′), Simpson dominance index (D), Pielou evenness index (E), and measurements of temperature, salinity, pH, total dissolved solids (TDS), and dissolved oxygen (DO). The results showed that only phytoplankton were detected, while no zooplankton were found. A total of 12 phytoplankton genera belonging to three phyla—Cyanobacteria, Bacillariophyta, and Chlorophyta—were identified. Bacillariophyta was the dominant group, while Navicula sp. was found at all stations. H′ was classified as moderate in the upstream (1.952) and middle (1.748) sections but low in the downstream section (0.673). E decreased from 0.786 upstream to 0.271 downstream, while D increased from 0.157 to 0.500. The physicochemical parameters showed that temperature and salinity were relatively stable, while the highest TDS value was recorded downstream. Overall, phytoplankton composition, diversity, evenness, and dominance indices, and physicochemical parameters indicated a gradient of ecological conditions along the Semangir River, with the downstream phytoplankton community exhibiting lower evenness and dominance by particular genera. These findings provide an empirical basis for using phytoplankton community structure and physicochemical parameters to monitor water quality in the Semangir River.